2013
DOI: 10.1002/ange.201308071
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Allyl Fluorides by Enantioselective Allylic Trifluoromethylation Based on Silicon‐Assisted CF Bond Cleavage

Abstract: Scheme 1. Kinetic resolution of MBH-type allyl fluorides 1 by enantioselective fluoroalkylation through CÀF bond activation/cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In 2014, Shibata and co-workers reported the first defluorinative AAA reaction (Scheme 2 ). 9 This pioneering work tackled the kinetic resolution of allyl fluorides 5 through asymmetric allylic trifluoromethylation with the Ruppert–Prakash reagent ( 6 ) catalyzed by (DHQD) 2 PHAL ( 9 ). The catalytic protocol simultaneously converts the racemic allyl fluoride 5 into a trifluoromethylated allylic compound 10 and the enantioenriched allyl fluoride ( R )- 5 , thereby enabling the asymmetric construction of two chiral fluorinated compounds in a single catalytic process.…”
Section: Lewis Base Catalyzed Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Shibata and co-workers reported the first defluorinative AAA reaction (Scheme 2 ). 9 This pioneering work tackled the kinetic resolution of allyl fluorides 5 through asymmetric allylic trifluoromethylation with the Ruppert–Prakash reagent ( 6 ) catalyzed by (DHQD) 2 PHAL ( 9 ). The catalytic protocol simultaneously converts the racemic allyl fluoride 5 into a trifluoromethylated allylic compound 10 and the enantioenriched allyl fluoride ( R )- 5 , thereby enabling the asymmetric construction of two chiral fluorinated compounds in a single catalytic process.…”
Section: Lewis Base Catalyzed Methodologiesmentioning
confidence: 99%
“…Subsequently, in 2016, the Shibata group expanded on his pioneering discoveries by developing a defluorinative asymmetric allylic trichloromethylation of allyl fluorides 5 with chloroform ( 15 ) as trichloromethylating agent (Scheme 3 ). 10 This elegant transformation, catalyzed by (DHQD) 2 PHAL ( 9 ) and triggered by the Ruppert–Prakash reagent ( 6 ), forms diverse trichloromethylated products 16 in good to excellent yields (46–97%) and with good enantiocontrol (91:9 to 98.5:1.5 er). The methodology can be successfully expanded to other nucleophilic species, including the terminal alkyne 19a , the polyfluorinated arene 19b , and indene 19c , as well as the fluorinated disulfone 19d , furnishing products 21a – d in moderate yields (38–73%) and with a slightly decreased enantiocontrol (80.5:19.5 to 98.5:1.5 er).…”
Section: Lewis Base Catalyzed Methodologiesmentioning
confidence: 99%
“…15a AQs are effective photosensitizers or photocatalysts due to their intense visible light absorption (400-750 nm), long excited state lifetime, high efficiency for ISC (inter-system crossing), and good thermal and photochemical stabilities. 42 trifluoromethylation of alkenes through allylic C-H bond activation, 44 allylic C-C bond activation through photoredox catalysis, 45 allylic halide activation through coupling reactions 46 or substitution reaction 47 and Morita-Baylis-Hillman adducts through nucleophilic substitution. 48 While talking about photoredox trifluoromethylation approaches via allylic C-H bond activation, in 2015 Akita et al reported a [Ru(bpy) 3 ] (PF 6 ) 2 -catalysed protocol for α-alkyl styrene substrates 30 using Umemoto's reagent 31 as a CF 3 source (Scheme 13).…”
Section: C(sp 3 )-H Trifluoromethylation/fluoroalkylationmentioning
confidence: 99%
“…demonstrated the kinetic resolution of fluorinated Morita‐Baylis‐Hillman adduct rac ‐ 76 by trifluoromethylation with CF 3 SiMe 3 using a chiral cinchona derivative (DFQD) 2 PHAL 75 as the catalyst (Scheme 20). [53] This reaction was triggered by S N 2’‐type C−F bond cleavage promoted by 75 as a nucleophile and CF 3 SiMe 3 as a C−F bond activator. Thus, the formed α,β‐unsaturated ester accepted the addition of the CF 3 anion in an enantioselective manner.…”
Section: Cross‐coupling Reactionsmentioning
confidence: 99%